Glucocorticoid Receptor Polymorphisms and Outcomes in Pediatric Septic Shock*. Issue 4 (April 2017) - Cvijanovich, Natalie Z.; Anas, Nick; Allen, Geoffrey L.; Thomas, Neal J.; Bigham, Michael T.; Weiss, Scott L.; Fitzgerald, Julie; Checchia, Paul A.; Meyer, Keith; Quasney, Michael; Gedeit, Rainer; Freishtat, Robert J.; et al.
Abstract : Objective: Polymorphisms of the glucocorticoid receptor gene are associated with outcome and corticosteroid responsiveness among patients with inflammatory disorders. We conducted a candidate gene association study to test the hypothesis that these polymorphisms are associated with outcome and corticosteroid responsiveness among children with septic shock. Design: We genotyped 482 children with septic shock for the presence of two glucocorticoid receptor polymorphisms (rs56149945 and rs41423247) associated with increased sensitivity and one glucocorticoid receptor polymorphism (rs6198) associated with decreased sensitivity to corticosteroids. The primary outcome variable was complicated course, defined as 28-day mortality or the persistence of two or more organ failures 7 days after a septic shock diagnosis. We used logistic regression to test for an association between corticosteroid exposure and outcome, within genotype group, and adjusted for illness severity. Setting: Multiple PICUs in the United States. Interventions: Standard care. Measurements and Main Results: There were no differences in outcome when comparing the various genotype groups. Among patients homozygous for the wild-type glucocorticoid receptor allele, corticosteroids were independently associated with increased odds of complicated course (odds ratio, 2.30; 95% CI, 1.01–5.21; p = 0.047). Conclusions: Based on these glucocorticoid receptor polymorphisms, we could not detect a beneficial effect of corticosteroids among any genotype group. Among children homozygous for the wild-type allele, corticosteroids were independently associated with increased odds of poor outcome.